Niwl Ddoe - Jones, Geraint Vaughan (Y Lolfa, 2021)
A woman's body in the River Dee, a tragedy in Llŷn, a lost novel, a secret diary, a perplexing family tree. Mystery lurks in the past of all of us, no more so than in the life of world-famous authoress Veronique and the family history of Sisial y Traeth in Abersoch. Journalist Huw Peris sets out to unravel a number of mysteries but will. Intro – Dydd Llun – Dydd Mawrth – Dydd Mercher – Dydd Iau – Dydd Gwener – Dydd Sadwrn – Dydd Sul – Bore Llun – Dydd Mawrth – Pedwar mis yn ddiweddarach Pnawn Mercher – Min nos yr un diwrnod – Dydd Iau – Dydd Sadwrn – Dydd Sul – Bore Llun – Dydd Mawrth – Amlosgfa Bangor, y dydd Mawrth canlynol – Llundain - min nos yr un diwrnod – Mynwent Llanengan, drannoeth – Nos Galan.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books